2021
DOI: 10.11114/ijce.v4i2.5350
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Secondary Physical Education

Abstract: There is a large quantity of research (Alguacil, 2018; Ciotto & Gagnon, 2018; McKenzie and Lounsbery, 2014) which states the importance Physical Education (PE) has in pupils’ lives. However, there is a state of decline for the status of the subject (Harris, 2018; Kirk et al., 2013). Parents perception is an under-researched area (Na, 2015; Yilmaz, 2018), especially in the UK, therefore, it is important parents’ beliefs are explored to understand an important stakeholder’s viewpoint. Purpose: To explore and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Earley and Fleet [41] claim that there are many clashing perspectives on the value of and reasons for PE. A similar conclusion arises from this study.…”
Section: Theme 1 Educating the Publicmentioning
confidence: 99%
“…Earley and Fleet [41] claim that there are many clashing perspectives on the value of and reasons for PE. A similar conclusion arises from this study.…”
Section: Theme 1 Educating the Publicmentioning
confidence: 99%
“…It is the question of the status of PE in the context of other subjects that encourages a deeper understanding not only of PE but also of the attitude of teachers of other subjects towards assessment in PE, which has so far been poorly studied. Some studies have found that parents of students have little interest in the goals and content of PE (Sheehy, 2011), although their attitudes towards PE in general (Earley, Fleet, 2021) and the fact that students are assessed are positive (James et al, 2005). However, we still know little about how parents believe children's achievement in PE should be assessed.…”
Section: Introductionmentioning
confidence: 99%